1998
DOI: 10.1046/j.1365-3148.1998.00136.x
|View full text |Cite
|
Sign up to set email alerts
|

The expression of the NB1 antigen on myeloid precursors and neutrophils from children and umbilical cords

Abstract: The neutrophil-specific antigen NB1 is expressed by neutrophils from 97% of healthy adults. However, membrane expression of this molecule is unique in that it is found on only a subpopulation of neutrophils present in NB1-positive adults. We have investigated the ontogeny of NB1 antigen expression by haematopoietic progenitor cells to determine the stage and pattern of antigen expression during granulocytic cell differentiation. In addition, we examined whether the ontogeny and frequency of granulocytic cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 8 publications
2
38
0
Order By: Relevance
“…[3][4][5][6][7][8][9] A special feature of NB1 is its expression on a neutrophil subpopulation. 10,11 Recently, we elucidated the primary structure of the NB1 glycoprotein. 12 A 1614-base pair (bp) cDNA codes for 437 amino acids (aa), of which 416 residues form an NH2-terminal extracellular protein with 2 cysteine-rich domains, 3 potential N-linked glycosylation sites, and a short segment including a glycosyl-phosphatidylinositol (GPI) attachment site.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9] A special feature of NB1 is its expression on a neutrophil subpopulation. 10,11 Recently, we elucidated the primary structure of the NB1 glycoprotein. 12 A 1614-base pair (bp) cDNA codes for 437 amino acids (aa), of which 416 residues form an NH2-terminal extracellular protein with 2 cysteine-rich domains, 3 potential N-linked glycosylation sites, and a short segment including a glycosyl-phosphatidylinositol (GPI) attachment site.…”
Section: Introductionmentioning
confidence: 99%
“…While NB1 and PRV-1 appear to be alleles of the same gene, some differences have been described in the expression of NB1 and PRV-1. NB1 gp is expressed by neutrophils and neutrophil precursors, but not by erythrocyte precursors or megakaryocytes (2,5,7). However, immunohistochemical staining of bone mar- row sections from patients with polycythemia vera showed that PRV-1 gp was expressed by early erythroblasts, megakaryocytes, promyelocytes, and myelocytes (13).…”
Section: Discussionmentioning
confidence: 99%
“…in the investigation of transfusion-related acute lung injury (TRALI), in population studies or in the analysis of potential changes during pregnancy [122][123][124][125][126][127]. Moreover, functional and morphologic changes of circulating neutrophil cells during plateletpheresis were investigated using flow cytometry [128].…”
Section: Granulocyte/monocyte Integrity and Immunologymentioning
confidence: 99%